Antibiotics Administered via Intravenous Push Versus Intravenous Piggyback to Adult Patients in the Emergency Department: a Randomized Trial - Rahbar, Aryan; Promlap, John; Patel, Jayme; David, Jason; Phan, Lisa; Lee, Perry; Zitek, Tony (SN comprehensive clinical medicine, 2023)
While antibiotics are frequently administered via intravenous piggyback (IVBP), intravenous (IV) push administration is easier and faster. Therefore, we compared the safety and efficacy of IV push to IVPB antibiotics in a randomized trial. This was a single center, double-blinded, double-dummy, randomized controlled trial on a convenience sample of emergency department patients receiving β-lactam antibiotics. Patients were randomized to receive the antibiotic either by IV push or by IVPB. Patients’ symptoms were assessed for 90 min following administration. The primary outcome was the percentage of patients experiencing a possible adverse drug reaction (ADR) within 90 min. The key secondary outcome was hospital length of stay. Between April 2018 and June 2019, 37 patients were randomized to IV push and 34 to IVPB. After 90 min, 4 patients (11.8%) in the IVPB group had a possible ADR, compared to 7 (18.9%) in the IV push group (difference 7.1% (95% CI − 9.5 to 23.8%)). Two patients had a grade 2 reaction; both received IV push antibiotics. No patients had higher than a grade 2 ADR in either group. Median hospital length of stay was 68.1 h for IV push and 68.6 h for IVPB (difference 0.5 (95% CI − 29.6 to 45.1)). There were no statistically significant differences in ADRs between IV push and IVPB antibiotic administration, but this study was too small to draw conclusions about safety. There was a signal of harm in the IV push group, which should be further explored. Administration by IV push did not reduce hospital length of stay. Trial Registration This study was prospective registered on clinicaltrials.gov on November 6, 2017 (NCT03360617).